Pengaruh Shopping Lifestyle dan Positive Emotion Terhadap Impulse Buying - Pipih Sopiyan; Neny Kusumadewi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
The purpose of this study was to determine the effect of Shopping Lifestyle and Positive Emotion on Impulse Buying both partially and simultaneously. This research is a type of survey research using descriptive and verification approaches. The object of consumer research shop UD Putra Tiga Saudara Majalengka.The results showed that 75.48% of consumers behaved in Shopping Lifestyle, 75.45% of consumers were in Positive Emotion conditions and 75.39% showed impulse buying behavior. Partially Shopping Lifestyle has a positive and significant effect on Impulse Buying with a contribution rate of 13.76%. Meanwhile, Positive Emotion has no effect on Impulse Buying with a contribution rate of 1.88%. However, simultaneous Shopping Lifestyle and Positive Emotion have a significant effect on Impulse Buying with a contribution rate of 15%. Seeing these results, it is important to do research again on the Positive Emotion variable.